The Impact Of Mixed Aerobic Exercise On The Body Mass Index (BMI) Of Employees With Sedentary Behavior - Syifa Nurul Fadhilah; Ahmad Hamidi; Sandey Tantra Paramitha (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
Adopting a sedentary lifestyle can elevate the likelihood of developing non-communicable illnesses like obesity and cardiovascular issues. Employees often engage in prolonged sedentary behaviour due to spending over 6 hours gazing at computer screens. This research endeavours to investigate the potential impact of mixed-impact aerobics on Body Mass Index (BMI) as well as its ability to lessen sedentary behaviour. The study employed a quasi-experimental design with a one-group pre-test-post-test design. Sixty individuals were chosen through purposive sampling and split into two groups, but only the experimental group consisting of 30 individuals underwent a pretest-posttest treatment that lasted for 8 weeks with a frequency of 3 treatments per week. The findings of the study indicated a significant impact on the incidence of BMI, as well as a reduction in sedentary behaviour, as evidenced by the values (p=0.001 and 0.0065 <0.05). This study shows that mixed-impact aerobic exercise has a significant effect on BMI and decreases sedentary behaviour in employees.